Case report: Pemigatinib-induced retinopathy: a serial examination of subretinal fluid secondary to an FGFR inhibitor - Barmas-Alamdari, Daniel; Jiao, George; Lieberman, Ronni (Frontiers in Ophthalmology, 2024)
Abstract Background Modern chemotherapeutic agents continue to evolve as modern monoclonal antibody treatments are designed to directly target proteins, enzymes, and focal loci. A particular class of these medications, fibroblast growth factor (FGFR) inhibitors, specifically pemigatinib (Pemazyre; Incyte), has been approved by the US Food and Drug Administration since April 2020 for the treatment of advanced or metastatic cholangiocarcinoma. As a relatively new medication, its side effect profile is manifesting in active clinical practice. The presence of FGFR receptors in the retinal pigment epithelium makes the retina susceptible to potential adverse effects secondary to its use. Case presentation A 69-year-old African American male with TMB-3 metastatic adenocarcinoma of the liver from primary cholangiocarcinoma undergoing chemotherapy with pemigatinib was found to have asymptomatic bilateral subretinal fluid accumulation. Serial monitoring with optical coherence tomography (OCT) demonstrated complete resolution of subretinal fluid while off-cycle and asymptomatic re-accumulation of subretinal fluid while on-cycle, with no significant changes in visual acuity. Conclusions Subretinal fluid accumulation secondary to pemigatinib may develop during active treatment cycles without causing any significant visual symptoms to the patient. Serial monitoring demonstrates fluctuations of subretinal fluid during the patient’s on and off-cycles. This case strengthens the current guidelines for continuing pemigatinib in asymptomatic patients found to have subretinal fluid. Further studies are warranted to identify patients who may be at higher risk for developing subretinal fluid.